The Impact of the Contextual Fit Enhancement Protocol on Behavior Support Plan Fidelity and Student Behavior. (August 2021) - Monzalve, Manuel; Horner, Robert H.
The contextual fit of a behavior support plan refers to the extent that the procedures of the plan are consistent with the knowledge, values, skills, resources, and administrative support of those who are expected to implement the plan. This study used a concurrent multiple baseline design across four participants to assess the presence of a functional relation between introduction of the Contextual Fit Enhancement Protocol, an intervention designed to improve contextual fit, and (a) an increase in fidelity of support plan implementation and (b) improved student behavior. Results indicate that following implementation of the Contextual Fit Enhancement Protocol, support plan implementation fidelity increased and student problem behavior decreased. In addition, teachers participating in the study rated the contextual fit intervention process as effective and efficient. Limitations and implications for future research, practice, and training are discussed.